Progression of adverse local tissue reaction in ASR metal-on-metal hip arthroplasty: a longitudinal MARS-MRI study at mid- to long-term. Issue 3 (May 2021) - Laaksonen, Inari; Galea, Vincent P; Connelly, James W; Matuszak, Sean J; Marega, Luca; Madanat, Rami; Muratoglu, Orhun; Malchau, Henrik
Background: Despite the large number of studies assessing adverse local tissue reaction (ALTR) in metal-on-metal (MoM) hip implants, there is still a lack of knowledge about the natural progression of ALTR. The aims of this study were to describe the natural course of changes in ALTR at mid- to long-term follow-up for patients treated with metal-on-metal hip arthroplasty and to determine possible risk factors associated with change in ALTR. Methods: A total of 158 patients (158 hips), 109 MoM hip resurfacing arthroplasties (HRAs) and 49 MoM total hip arthroplasties (THAs), with 2 clinical follow-ups including MARS-MRIs were included. The mean time from index operation to the first visit was 7.6 years (range 3.4–11.4 years), and the mean time between the 2 visits was 1.0 year (range 0.7–1.6 years). Results: The proportion of patients with moderate or severe ALTR did not increase significantly between the first and second visit for the MoM HRA group (14.7–15.6%; p = 0.850) or the MoM THA group (32.7–36.7%; p = 0.671). 8 (7.3%) HRA patients and 9 (18.4%) THA patients progressed in ALTR grade. None of the collected clinical variables was sensitive or specific in identifying patients with ALTR progression. Conclusions: Although ALTR prevalence was high in our cohort, clinically significant ALTR progression was rare. We were unable to find any predictors associated with ALTR change. This indicates that MARS-MRI remains a valuable tool in the follow-up of patients treated with MoM hip devices in identifying patients who may need revision surgery.